Nonflammable UV protective films consisting of clay and lignin with tunable light/gas transparency. Issue 38 (2nd July 2021) - Shikinaka, Kazuhiro; Suzuki, Asami; Otsuka, Yuichiro
Abstract : Nonflammable UV protective films consisting of clay and lignin with tunable light/gas transparency were prepared. Abstract : In this paper, we present nonflammable UV protective films consisting of clay minerals and lignin derivatives. The nonflammable transparent films were produced by mixing clay with a lignin derivative extracted from plants by simultaneous enzymatic saccharification and comminution. The preparation procedure did not require hazardous chemicals. The optical properties and gas permeability of the films could be tuned by the components and phase separation structure of the clay minerals and lignin derivatives. In particular, the gas transmittance of the films could be controlled in the range of several mol m −2 s −1 Pa −1 . The present film uses mineral and plant components as high-value industrial materials and reduces the environmental load of extracting limited petroleum-based resources.